HUBUNGAN ANTARA POWER ENDURANCE OTOT LENGAN DAN POWER ENDURANCE OTOT TUNGKAI DENGAN KECEPATAN RENANG GAYA DADA 50 METER - Sandi Prasetia Parela, sandi-parela (2017)
This research is motivated by the importance of the components of the physical condition to the results of 50-meter breaststroke swimming speeds such as power endurance arm muscle and leg muscle endurance power. The purpose of this research is to figure out the relationship between power endurance of arm muscle and power endurance of leg muscle with result of 50 meter breaststroke velocity. This research uses descriptive method with correlation technique. The sample used in this research is the member of UKM aquatic UPI Bandung as many as 10 people taken by using purposive sampling technique. Instruments used in this study are a pull up test, hurdle jump test, and 50-meter breaststroke swimming speed test. Shows there is a power endurance relationship of arm muscle and leg muscle endurance power to 50 meter breaststroke swimming speed. With the result of power endurance research arm muscle to swimming speed is r = - 0.861, sig value. 0.001 <0.05, power leg endurance power endurance against swimming speed = -0.937, sig value. 0.000 <0.05, the result of power endurance research of arm muscle and endurance power of leg muscle to swimming speed is r = 0.937, sig value. 0.001 <0.05.